2022
DOI: 10.3389/fphar.2022.971905
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer regimens containing third generation taxanes SB-T-121605 and SB-T-121606 are highly effective in resistant ovarian carcinoma model

Abstract: Taxanes are widely used in the treatment of ovarian carcinomas. One of the main problems with conventional taxanes is the risk of development of multidrug resistance. New-generation synthetic experimental taxoids (Stony Brook Taxanes; SB-T) have shown promising effects against various resistant tumor models. The aim of our study was to compare the in vitro efficacy, intracellular content, and in vivo antitumor effect of clinically used paclitaxel (PTX) and SB-Ts from the previously tested second (SB-T-1214, SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…All tested SB-Ts were more effective than PTX (IC 50 27.62 ± 1.40 nM and 22.41 ± 1.95 nM for Paca-44 and BxPC-3 cell lines, respectively. ( Figure 1 A) However, unlike in our study analyzing PTX-resistant ovarian cancer cells NCI/ADR-RES, 14 where SB-Ts at the highest concentrations after 72 h of incubation caused a reduction in cell viability to 3.6–4.3% of the control, the same incubation time led to the reduction of the Paca-44 cell line viability to 48.1 ± 4.3%, 41.3 ± 6.2%, 33.0 ± 4.3%, and 44.4 ± 1.8% for PTX, SB-T-1216, SB-T-121605, and SB-T-121606, respectively. The viability of BxPC-3 cells was reduced to 27.3 ± 3.7%, 17.1 ± 4.2%, 18.2 ± 1%, and 16.1 ± 2.2% for PTX, SB-T-1216, SB-T-121605, and SB-T-121606, respectively.…”
Section: Resultscontrasting
confidence: 66%
See 4 more Smart Citations
“…All tested SB-Ts were more effective than PTX (IC 50 27.62 ± 1.40 nM and 22.41 ± 1.95 nM for Paca-44 and BxPC-3 cell lines, respectively. ( Figure 1 A) However, unlike in our study analyzing PTX-resistant ovarian cancer cells NCI/ADR-RES, 14 where SB-Ts at the highest concentrations after 72 h of incubation caused a reduction in cell viability to 3.6–4.3% of the control, the same incubation time led to the reduction of the Paca-44 cell line viability to 48.1 ± 4.3%, 41.3 ± 6.2%, 33.0 ± 4.3%, and 44.4 ± 1.8% for PTX, SB-T-1216, SB-T-121605, and SB-T-121606, respectively. The viability of BxPC-3 cells was reduced to 27.3 ± 3.7%, 17.1 ± 4.2%, 18.2 ± 1%, and 16.1 ± 2.2% for PTX, SB-T-1216, SB-T-121605, and SB-T-121606, respectively.…”
Section: Resultscontrasting
confidence: 66%
“…In this pivotal experiment, we demonstrated that the combination of a high dose of conventional PTX with a low dose of the third-generation SB-T is very effective combination regimen. In line with our previous in vitro and in vivo observations of increased systemic toxicity of high doses of third-generation SB-Ts in monotherapy, 14 we used their low dose combination with a high-dose PTX, which is relatively safe. This adjustment allowed us to follow the “three R″ principles in animal research, especially aimed at the reduction of the number of animals and refinement, because the high toxicity of monotherapy of SB-Ts could be avoided.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations